Ductal carcinoma in situ: single center experience with 5-year follow-up - Gudavičienė, Daiva; Židonis, Žygimantas (Lietuvos chirurgija, 2016)
IntroductionDuctal carcinoma in situ (DCIS) – heterogeneous group of diseases. Numbers of DCIS after introduction of breast cancer screening program, is constantly rising. Material and methodsA retrospective analysis of 31 DCIS patient treated at National Cancer Institute in 2010 was performed. Patient ‘s age was 46– 75 years, average 60 y. 51.6% of cases were high grade DCIS, 9.6 % intermediate grade, 32.2 % low grade DCIS, and 3.2% Paget disease. 61.3% of cases were oestrogen positive (7–8 acc. Allred), and in 32.2 % of cases oestrogen receptors were negative. 61.3% of DCIS were progesterone positive, and in 35.5% progesterone receptors were negative. Usually DCIS was diagnosed performing mammography and radio-guided stereotactic biopsy, 67.7 %. In 70.1% radiologist evaluated mammography BI-RADS 4–6. In 45% radio-guided biopsy, and in 29.0% fine needle biopsy was performed.ResultsPatients were followed-up for 5 years. One patient died from ovarian cancer 60 month after DCIS surgery, and in 1 axillary metastases were found 61 months after DCIS surgery.ConclusionsAge average of DCIS patients was 60 y., high grade DCIS, oestrogen and progesterone positive DCIS was dominant. After 5-year follow-up progression of disease, axillary metastases, was found in one patient (3,2 %).
Keywords: breast cancer; ductal carcinoma in situ; wide local excision